Peran Badan Amil Zakat Nasional (BAZNAS) Provinsi Bengkulu dalam Meningkatkan Perekonomian Masyarakat Melalui Program Z-Mart - Jemi Puspita sari; Asnaini Asnaini; Katra Pramadeka (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2025)
The rise of modern retail market businesses means small scale micro businesses are experiencing a lack of interest. This is due to the limited availability of trading materials for sale and limited capital.  The National Zakat Amil Agency is one of the official zakat management institutions in Indonesia that distributes zakat productively. One of BAZNAS' flagship programs is Z-Mart, which aims to empower mustahik through developing zakat-based retail businesses. This program not only provides business capital assistance, but also training, mentoring and professional business management to the beneficiaries. The aim of this research is to analyze the role of BAZNAS Bengkulu Province in improving the community's economy through the Z-Mart program. This stage includes implementation, distribution of funds and development of the Z-Mart program. Using qualitative descriptive methods, data was collected through observations and interviews with mustahik who received the Z-Mart program and BAZNAS Bengkulu Province in the field of collecting funds and utilizing zakat funds. These findings emphasize the importance of targeted distribution and community empowerment through coaching so that they can be productive and independent. This process cannot be separated from the aim of the Z-Mart program so that the sustainability of mustahik businesses can increase and mustahik become more independent..